2013
DOI: 10.1097/iop.0b013e3182831c49
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Development as a Function of Age in Indigenous North American Skeletons

Abstract: This largest direct-measure study of pediatric orbital volume suggests that orbital growth continually decelerates from birth until maturity at 22 years. With 50% of orbital growth occurring by 16 months of age, surgeons removing periocular vascular anomalies after that age should consider concurrent skeletal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies have explored the structure of the human orbits and its relationship with demographic and clinical parameters. Notable variability was found among different ethnic groups [11][12][13] and it was actually reported that orbital regions might display the greatest variation among facial measurements in both sexes [14]. Gender is another significant and independent factor of orbital and eyeball dimensions as reported in the literature [15][16][17], which also reflects the greater skull dimensions in men compared to women [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the structure of the human orbits and its relationship with demographic and clinical parameters. Notable variability was found among different ethnic groups [11][12][13] and it was actually reported that orbital regions might display the greatest variation among facial measurements in both sexes [14]. Gender is another significant and independent factor of orbital and eyeball dimensions as reported in the literature [15][16][17], which also reflects the greater skull dimensions in men compared to women [18].…”
Section: Discussionmentioning
confidence: 99%
“…According to our findings, both TB and BB groups showed a slight increment of the orbital volume at T2 (respectively 0,64 cm 3 and 0,77 cm 3 ) that was statistically significant; this is in agreement with previous findings showing that the orbital volume increased of 0.72 cm 3 after treatment with maxillary expander. Due to the absence of a control group, these findings should be taken with some caution since part of this volumetric increment could be attributed to the potential residual grow of this region that reach almost 90% at the age of almost 17 years [32,33] (slight above the mean age of the subjects included in this study). Despite we accepted the null hypothesis of the study since the volumetric increment of the orbital cavity was statistically significant greater in the BB group, it remains questionable if the mean difference of post-treatment orbital changes between the two groups, i.e.…”
Section: Discussionmentioning
confidence: 99%